FROM DISCRIMINATION TO INCLUSION: LEGAL PERSPECTIVES ON PROTECTING TRANSGENDER RIGHTS IN THE WORKPLACE - Bhatnagar, Astha; Asthana, K.B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Emphasising the legal, ethical, and social challenges faced by transgender employees, this paper examines the development and current situation of transgender rights in the workplace. Starting with the historical evolution of transgender rights, it moves to important legal events such as Price Waterhouse v. Hopkins (1989), Macy v. Holder (2012), and the key Bostock v. Clayton County (2020) ruling thereby affording Title VII protections to transgender persons. Notwithstanding these developments, research reveals ongoing disparities in legal protections between many nations motivated by tensions between transgender rights and other human rights concerns including freedom of expression and religious views. The paper also covers the moral consequences of workplace discrimination and the major part companies play in creating inclusive surroundings. Legal and policy proposals demand Title VII to be changed to particularly safeguard transgender people, improve enforcement policies, and apply thorough federal statutes offering consistent protections. The last point emphasises the need of improving legal rights and building inspiring environments to achieve real inclusion for transgender people, therefore promoting a more fair and equal society.